2020
DOI: 10.1371/journal.pone.0229089
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid derived suppressor cells contribute to the malignant progression of oral squamous cell carcinoma

Abstract: The tumor-related myeloid derived suppressor cells (MDSCs), important immunosuppressive cells in tumor microenvironment, play an important role in the cancer progression. This study is aimed to investigate the crosstalk between MDSCs and oral squamous cell carcinoma (OSCC) cells and their role in the malignant progression of OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 50 publications
0
33
0
1
Order By: Relevance
“…MDSCs possess a strong immunomodulatory capacity, being recruited during inflammatory/infectious processes [31]. In the oral mucosa, MDSCs have mainly been studied in relation to oral squamous cell carcinomas, as they facilitate cancer growth and immune evasion by suppressing T cells [32][33][34]. MDSCs are related to resident macrophages and can actually differentiate into macrophages [31].…”
Section: Tolerance Mediated By Dendritic Cellsmentioning
confidence: 99%
“…MDSCs possess a strong immunomodulatory capacity, being recruited during inflammatory/infectious processes [31]. In the oral mucosa, MDSCs have mainly been studied in relation to oral squamous cell carcinomas, as they facilitate cancer growth and immune evasion by suppressing T cells [32][33][34]. MDSCs are related to resident macrophages and can actually differentiate into macrophages [31].…”
Section: Tolerance Mediated By Dendritic Cellsmentioning
confidence: 99%
“…Consistent with this, Ren et al have indicated that early-stage MDSCs of peripheral blood and tumor-infiltrating early-stage MDSCs can upregulate arginase-1 [ 40 ]. Besides, the co-culture of MDSCs with tumoral cells can upregulate arginase-1 expression in MDSCs [ 41 ]. Although the exact mechanism of TIGIT and PD-1 co-expression has not been exactly identified in tumors, the currently available evidence indicates that TIGIT and PD-1 can both increase arginase-1 activity, which can ultimately lead to T cells anergy and the development of immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pang et al . reported that the MDSCs number was increased in the tissue of oral squamous cell carcinoma (OSCC) patients, which was positively associated with lymph node metastasis, pathological grade, T stage, and poor prognosis [ 14 ]. In a prospective cohort study, Kim et al .…”
Section: Immune Response In Head and Neck Cancermentioning
confidence: 99%